De inedito atque ignoto carmine Sigismundi Chisii, 1649–1678 - Sacré, Theodoricus (Nordlit, 2014)
This article presents an unpublished Neo-Latin poem written by Sigismondo Chigi (1649–1678), a nephew of Fabio Chigi or Pope Alexander VII (1655–1667). It was written in Rome in the early 1660s and deals with the times of Agostino Chigi il Magnifico, one of the richest persons in the Roman world of the early sixteenth century. Sigismondo’s humorous poem is considered against the background of the Latin poetry of his uncle, the later Pope, who tutored Sigismondo’s Latin studies, handed over his own poetry and other Latin writings to his nephew, and tried to make him aware of the importance of the Chigi family in a Roman context. The poem is preserved in a Vatican manuscript.